2016
DOI: 10.1039/c5fd00210a
|View full text |Cite
|
Sign up to set email alerts
|

Photo-spectroscopy of mixtures of catalyst particles reveals their age and type

Abstract: Within a fluid catalytic cracking (FCC) unit, a mixture of catalyst particles that consist of either zeolite Y (FCC-Y) or ZSM-5 (FCC-ZSM-5) is used in order to boost the propylene yield when processing crude oil fractions. Mixtures of differently aged FCC-Y and FCC-ZSM-5 particles circulating in the FCC unit, the so-called equilibrium catalyst (Ecat), are routinely studied to monitor the overall efficiency of the FCC process. In this study, the age of individual catalyst particles is evaluated based upon photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…This industrial approach consisted of a permanent rolling magnet cylinder under a belt where particles with different sizes were fed on, to sort them in just two fractions. [40] In this work, however, the particles have been pre-sorted by size and we focus on the relation of Fe content, magnetic properties and the availability of Brønsted acid sites [41][42][43][44] in a wide range of Fe content and on real, industrially processed ECAT particles, providing a unique catalyst diagnostics platform for single particle analysis.…”
Section: Recent Advances In Microfluidics Open New Ways To Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This industrial approach consisted of a permanent rolling magnet cylinder under a belt where particles with different sizes were fed on, to sort them in just two fractions. [40] In this work, however, the particles have been pre-sorted by size and we focus on the relation of Fe content, magnetic properties and the availability of Brønsted acid sites [41][42][43][44] in a wide range of Fe content and on real, industrially processed ECAT particles, providing a unique catalyst diagnostics platform for single particle analysis.…”
Section: Recent Advances In Microfluidics Open New Ways To Workmentioning
confidence: 99%
“…Previous work demonstrated that the Brønsted acid-catalysed oligomerization of 4-methoxystyrene visualizes zeolite domains by fluorescence micro-spectroscopy. [43,44,48] This fluorescence was used as a measure for acidity by averaging the fluorescence intensity per particle over AE 100 ECAT particles for all five fractions.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Imaging methods, some of them quite novel in catalysis research, 7,8 were also used widely in the work reported at the Faraday Discussion, and these included characterization of zeolitecontaining cracking catalysts investigated on the scale of microns. Important components of industrial catalysts for hydrocarbon cracking in the manufacture of petrol incorporate binders and amorphous components in addition to zeolite crystallites, and results presented at the Faraday Discussion demonstrate their high degrees heterogeneity-on the scale of micronsperhaps a surprising result in view of the enormous scale of application of cracking catalysts.…”
Section: Catalyst Characterization By X-ray Diffraction Spectroscopymentioning
confidence: 99%
“…This industrial approach consisted of a permanent rolling magnet cylinder under a belt where particles with different sizes were fed on, to sort them in just two fractions. 42 In this work, however, the particles have been pre-sorted by size and we focus on the relation of Fe content, magnetic properties and the availability of acid sites [43][44][45][46] in a wide range of Fe content and on real, industrially processed FCC ECAT particles, providing a unique catalyst diagnostics platform for single particle analysis.…”
Section: Chaptermentioning
confidence: 99%
“…The oligomerization of 4-methoxystyrene is catalysed by the Brønsted acid sites in zeolite domains and induces fluorescence. 40,45,46 This fluorescence was used as a measure for acidity by averaging the fluorescence intensity per particle over ± 100 catalyst particles for all five fractions. These average intensities were compared with Nile blue A staining results.…”
Section: Acidity and Accessibility Of Sorted Fcc Particlesmentioning
confidence: 99%